First partial mitogenome of a new Seira Lubbock species (Collembola,Entomobryidae, Seirinae) from Cambodia reveals a possible separate lineage from the Neotropical Seirinae - Godeiro, Nerivania Nunes; Zhang, Feng; Cipola, Nikolas Gioia (Zootaxa, 2020)
A new species of Seira from Koh Rong Sanloem Island, Cambodia, as well as its mitochondrial genome information, are herein described. Seira sanloemensis sp. nov. has a similar colour pattern compared to nine other species of Seira worldwide distributed, but the dorsal chaetotaxy is more similar to S. arunachala Mitra from India, S. camgiangensis Nguyễn from Vietnam, and S. gobalezai Christiansen & Bellinger from Hawaii. However, the new species differs from these species by dorsal chaetotaxy of head, Th II–III and Abd II, collophore chaetotaxy, and morphology of the empodial complex. This is the third Collembola species described for Cambodia. Its assembled incomplete mitogenome from MGI reads, has a length of 13,953 bp, and contains all protein-coding genes except for tree tRNAs missing; the gene order is the same of the Pancrustacean ancestral gene order. Based on the alignment of the 13 coding genes, a maximum likelihood phylogenetic tree of medium bootstrap values suggested that the Asian Seira species can represent a different lineage from the Neotropical Seirinae, but further biogeographic and divergence estimation analyses plus the inclusion of more Asian taxa are necessary to test such hypothesis.